The Vlachs in contemporary Balkans (20th–21st century). Signs of distinctiveness and assimilation - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2021)
The aim of the article is to show different aspects of diversity among the Vlachs in the contemporary socio-political realities of the particular countries in South-Eastern Europe. Their diversity leads to a general threefold description. Most commonly the Vlachs are regarded as a cultural or regional minority (in Greece, Bulgaria, Croatia), they are identified with the Romanian nation (Bulgaria, Romania), or seen as an ethnic and language minority (North Macedonia, Albania). The communities of Vlachs had shaped their customs, traditions and identity in relation to their local living conditions. They were forced to find a modus vivendi with the dominant Slavic, Greek or Albanian-speaking population, as well as their local codes of conduct. As a result, the dispersed communities have never developed a uniform ethnic or cultural identity, which would bind them into a greater whole. What differentiates them further, is their legal and political situation in the particular countries of residence.